Electron-Ion Temperature Relaxation in Warm Dense Hydrogen Observed With Picosecond Resolved X-Ray Scattering - Fletcher, L. B.; Vorberger, J.; Schumaker, W.; Ruyer, C.; Goede, S.; Galtier, E.; Zastrau, U.; Alves, E. P.; Baalrud, S. D.; Baggott, R. A.; Barbrel, B.; Chen, Z.; et al. (Frontiers in Physics, 2022)
Angularly resolved X-ray scattering measurements from fs-laser heated hydrogen have been used to determine the equilibration of electron and ion temperatures in the warm dense matter regime. The relaxation of rapidly heated cryogenic hydrogen is visualized using 5.5 keV X-ray pulses from the Linac Coherent Light (LCLS) source in a 1 Hz repetition rate pump-probe setting. We demonstrate that the electron-ion energy transfer is faster than quasi-classical Landau-Spitzer models that use ad hoc cutoffs in the Coulomb logarithm.